לפשט את זה? (+ 3) ³ + (a-3) ³

לפשט את זה? (+ 3) ³ + (a-3) ³
Anonim

תשובה:

#color (מגנטה) (=> 18a ^ 2 + 27 #

#color (מגנטה) (=> 9 (2a ^ 2 + 3) #

הסבר:

שימוש בזהויות:

#color (אדום) ((+ b) ^ 3 = a ^ 3 + 3a ^ 2b + 3ab ^ 2 + b ^ 3 #

#color (אדום) (a-b) ^ 3 = a ^ 3-3a ^ 2b + 3ab ^ 2-b ^ 3 #

אנחנו מקבלים: # (a + 3) ^ 3 + (a-3) ^ 3 #

(3) ^ 3 (3) ^ 3 (3) ^ 3 + 3a 3 + 3a 3 (3) ^ 3 + 3) #

(3a * 9) + 27 (+) ביטול ביטול (3 +) + 9a ^ 2 + ביטול (3a * 9) + 27-

#color (מגנטה) (=> 18a ^ 2 + 27 #

#color (מגנטה) (=> 9 (2a ^ 2 + 3) #

~ מקווה שזה עוזר!:)